Randomised clinical trial: safety, tolerability, pharmacokinetics, and pharmacodynamics of single and multiple oral doses of tegoprazan (CJ‐12420), a novel potassium‐competitive acid blocker, in healthy male subjects. Issue 7 (22nd August 2019) - Han, Sungpil; Choi, Hee Youn; Kim, Yo Han; Nam, Ji Yeon; Kim, Bongtae; Song, Geun Seog; Lim, Hyeong‐Seok; Bae, Kyun‐Seop
Summary: Background: Tegoprazan (CJ‐12420) is a potassium‐competitive acid blocker (P‐CAB) with therapeutic potential for gastro‐oesophageal reflux disease (GERD) by reversibly suppressing gastric H + /K + ‐ATPase. Aims: To investigate the safety, tolerability, pharmacokinetics and pharmacodynamics of tegoprazan Methods: A phase I, randomised, double‐blind and placebo‐controlled clinical trial was conducted in 56 healthy male subjects without Helicobacter pylori infection. In the single ascending dose study, 50, 100, 200 and 400 mg tegoprazan were administered to 32 subjects. In the multiple ascending dose study, 100 and 200 mg tegoprazan were administered every 24 hours to each of the eight subjects for 7 days. In the comparative pharmacodynamics study, 40 mg esomeprazole was administered to eight subjects every 24 hours for 7 days. The assessment included safety, tolerability, pharmacodynamics through monitoring of 24‐hour gastric pH and pharmacokinetics of tegoprazan in plasma and urine. Results: Tegoprazan was generally well tolerated. Most adverse events reported in the study were mild in intensity and resolved without any sequelae. Exposure to tegoprazan increased in a dose‐proportional manner. Multiple dosing with tegoprazan showed no accumulation in plasma on day 7. The pharmacodynamic analysis revealed that tegoprazan showed rapid, dose‐dependent gastric acid suppression. Conclusions: Tegoprazan was well tolerated and showed rapid and potent gastric acid suppression. This supports the further development of tegoprazan as a treatment for acid‐related disorders.